Development and Effects of Computer-Based Self-Learning Instructional Puzzles on Junior Secondary School Students’ Learning Outcomes and Retention in Social Studies (2014)
Secondary school students‟ poor academic achievement in social studies has been attributed to the predominance of inappropriate instructional strategies in the teaching and learning of the subject. Scholars have recommended the use of a strategy that provides students with hands-on activities. Researches have shown the effectiveness of Computer-based Self-learning Instructional Puzzles (CSIP) in science related subjects but the use has not been given prominence in social studies. This study, therefore, designed, developed and determined the effects of computer-based self-learning instructional puzzles on Junior Secondary School students‟ learning outcomes and retention in social studies in Osun State. The moderating effects of gender and cognitive style were also examined. The study was in two phases. The first phase was the design and development of the CSIP using CSIP Model. The second phase determined the effects of the package on Junior Secondary School (JS) II students‟ learning outcomes and retention in social studies. This phase adopted pretest-posttest quasi-experimental research design using 2x3x2 factorial matrix. One hundred and forty one JS II students from four purposively selected schools were randomly assigned to CSIP and conventional teaching strategy groups while the treatment lasted 14 weeks. Two research questions were answered and eight hypotheses tested at 0.05 level of significance. The CSIP Instructional Package Evaluation Questionnaire (r = 0.82), Students‟ Attitude towards Social Studies Questionnaire (r = 0.73), Social Studies Achievement Test (r = 0.89), Cognitive Style Checklist, Instructional Package Perception Questionnaire (r = 0.84), Instructional Guide on Computer-based Instructional Strategy and Instructional Guide on Conventional Teaching Strategy were used for data collection. Data were analysed using mean, standard deviation, Pearson‟s product moment correlation, Analysis of Covariance and Scheffe‟s post-hoc test. The design of the package was rated appropriate in terms of functionality and navigation ( ̅ = 3.72), content and graphic evaluation ( ̅ = 3.66) and usability assessment ( ̅ = 3.62). Students‟ acceptance of the instructional package was also rated as follows: Perceived Usefulness ̅ = 3.24) and Perceived Ease of Use ( ̅ = 3.14). The correlation between students‟ perceived usefulness and perceived ease of use was significantly positive (r = 0.49) implying that the perceived usefulness of the package enhanced the use. There was a significant main effect of treatment on students‟ achievement (F(1,128)=162.00; η2 = .559). The CSIP group had a higher achievement mean score ( ̅ = 36.03) than the conventional group ( ̅ = 21.69). There was a significant main effect of treatment on students‟ retention (F(1,128) = 111.85; η2 = .446). The CSIP group had a higher retention score ( ̅= 32.63) than the conventional group ( ̅ = 21.69). There was no significant main effect of gender and cognitive style on students‟ attitude, achievement and retention in social studies. The computer-based self-learning instructional puzzle package was an acceptable strategy to social studies students at Junior Secondary School level and also enhanced their achievement and retention in the subject regardless of sex and cognitive style. Hence, the strategy should be adopted in teaching social studies in classroom.